ChemInform Abstract: Eu2+‐Activated Full Color Orthophosphate Phosphors for Warm White Light‐Emitting Diodes. Issue 49 (9th December 2014) - Zhao, Chenglong; Xia, Zhiguo; Li, Molin
Abstract RbBaPO4:0.03Eu2+ (I), NaCaPO4:0.01Eu2+ (II), and CsMgPO4:0.07Eu2+ (III) phosphors are prepared by solid state reaction of stoichiometric mixtures of A2CO3 (A: Rb, Na, Cs), MCO3 (M: Ba, Ca), (MgCO3)4·Mg (OH)2·5H2O, (NH4)2HPO4, and Eu2O3 (alumina crucibles, CO atmosphere, 1150 °C, 3 h).